2017
DOI: 10.1246/bcsj.20160389
|View full text |Cite
|
Sign up to set email alerts
|

Widely Tunable Plasmon Resonances from Visible to Near-Infrared of Hollow Silver Nanoshells

Abstract: Tuning of localized surface plasmon resonance (LSPR) of metal nanostructures has attracted a great deal of interest, and the controlled syntheses of them have been extensively studied for fine tuning of their LSPR. In this paper, we report widely tunable LSPR from visible to near-infrared of hollow silver nanoshells synthesized by reduction of silver thiocyanate. The silver nanoshell exhibits size- and thickness-dependent LSPR for symmetric dipole mode from visible to near-infrared regions, while the antisymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 51 publications
0
23
2
Order By: Relevance
“…Smith et al used flake particles in the binder to make colorful energy-efficient coatings that reduce solar absorptance with respect to other commercial paints that gives the same color output. Use of plain and core–shell nanoparticles to produce color is studied by Yong et al Tunability of plasmon resonances in the visible wavelength for the core–shell particle has been further inspected by Kado et al In this study, we demonstrate that colored surfaces with positive net radiative cooling power can be achieved by embedding plain and core–shell nanoparticles in a silica matrix.…”
mentioning
confidence: 60%
“…Smith et al used flake particles in the binder to make colorful energy-efficient coatings that reduce solar absorptance with respect to other commercial paints that gives the same color output. Use of plain and core–shell nanoparticles to produce color is studied by Yong et al Tunability of plasmon resonances in the visible wavelength for the core–shell particle has been further inspected by Kado et al In this study, we demonstrate that colored surfaces with positive net radiative cooling power can be achieved by embedding plain and core–shell nanoparticles in a silica matrix.…”
mentioning
confidence: 60%
“…Noble‐metal nanocrystals (NCs) are very important for applications in fields such as electrochemistry, electronics, magnetic storage, catalyst, and biotechnology . The properties of a metal NC are dependent on its morphology, including size and shape .…”
Section: Introductionmentioning
confidence: 99%
“…Noble-metal nanocrystals (NCs) are very important for applications in fields such as electrochemistry,e lectronics, magnetic storage, catalyst, andb iotechnology. [1][2][3][4][5][6][7][8][9][10][11][12][13] The properties of a metal NC are dependento ni ts morphology, including size and shape. [1][2][3][4][5][6] Therefore, many methods for the preparation of NCs with various shapes, such as nanoflowers, [14][15][16][17] nanocubes, [18][19][20][21] nanorods, [22][23][24] and nanowires, [25][26][27][28][29][30][31] with the desired properties have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, to date there are not a substantial quantity of reports on nanoshells capable of supporting LSPR bands at Telecom wavelengths, and the sensitivities reported in the VIS are low when compared to the other geometries [ 192 , 193 ]. Two of the scarce examples on the use of nanoshells at Telecom wavelengths is the one reported in [ 3 ], where the authors reported an etched FBG functionalized with nanoshell NPs, as a refractometric sensor for RI values from 1.333 to 1.346.…”
Section: Nanostructuresmentioning
confidence: 99%